Autonomiczność i specyfika regulacji niewypłacalności spółdzielni – wybrane problemy - Kruczalak-Jankowska, Joanna (PRAWO i WIĘŹ, 2024)
The issue of cooperative insolvency in Poland is relatively insignificant in terms of the number of debtors involved in these proceedings in recent years. Nevertheless, the insolvency of a cooperative evokes considerably stronger emotions in a somewhat different manner than in the case of a company. This is due, in part, to the special social role that is still attributed to cooperatives in the common opinion. Since 1920, the insolvency of cooperatives has been characterised by a certain degree of autonomy. The paper highlights the necessity to consider the specific symptoms of a financial crisis that are characteristic of entities engaged in professional business activities, despite the autonomy of cooperative insolvency. It is incumbent upon the competent management board in a cooperative to be aware of the consequences of such a crisis and the risk of personal civil and financial liability for failure to take action, which burdens its members in such a situation.